Ribotoxic Proteins, Known as Inhibitors of Protein Synthesis, from Mushrooms and Other Fungi According to Endo’s Fragment Detection - Nicola Landi; Hafiza Z. F. Hussain; Paolo V. Pedone; Sara Ragucci; Antimo Di Maro (Toxins, 2022)
rRNA N-glycosylases (EC 3.2.2.22) remove a specific adenine (A4324, rat 28S rRNA) in the sarcin ricin loop (SRL) involved into ribosome interaction with elongation factors, causing the inhibition of translation, for which they are known as plant ‘ribosome inactivating proteins’ (RIPs). However, protein synthesis inactivation could be the result of other enzymes, which often have rRNA as the target. In this scenario, Endo’s assay is the most used method to detect the enzymes that are able to hydrolyze a phosphodiester bond or cleave a single N-glycosidic bond (rRNA N-glycosylases). Indeed, the detection of a diagnostic fragment from rRNA after enzymatic action, with or without acid aniline, allows one to discriminate between the N-glycosylases or hydrolases, which release the β-fragment after acid aniline treatment or α-fragment without acid aniline treatment, respectively. This assay is of great importance in the mushroom kingdom, considering the presence of enzymes that are able to hydrolyze phosphodiester bonds (e.g., ribonucleases, ribotoxins and ribotoxin-like proteins) or to remove a specific adenine (rRNA N-glycosylases). Thus, here we used the β-fragment experimentally detected by Endo’s assay as a hallmark to revise the literature available on enzymes from mushrooms and other fungi, whose action consists of protein biosynthesis inhibition.